LITERACY EDUCATION URGENCY FOR CENTENNIAL GENERATION IN INDUSTRIAL REVOLUTION 4.0 - Muhamad Yusuf; Mira Zuzana; Doli Witro (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2020)
When talking about children’s abilities, they indeed cannot be separated from their educational or training background. Moreover, he has entered the working age that must have productivity in his work, especially at this time, where the era has entered the industrial revolution 4.0. The industrial revolution 4.0 is marked by the development of digitalization in various lines of life. On the one hand, the industrial revolution 4.0 had many positive impacts. However, on the other hand, as the McKinsey Global Institute states that as a result of the 4.0 industrial revolution in the next five years, there will be 52.6 million jobs that will decline and even disappear. This certainly will be a challenge for the centennial generation (children born from 1996-2011) at this time, which they have to survive with the existing conditions and situations. This paper will discuss several factors that describe and address issues such as what is meant by the centennial generation, literacy, and the urgency of literacy education for the centennial generation in the digital age. According to authors, thi is essential to discuss, given the increasingly rapid development and technological progress resulting in the loss of much work.